Improving community livelihoods by recovering and developing their traditional crops - Baena, M.; Galluzzi, G.; Padulosi, S. (2012)
When crops that could contribute to better food, health and income are abandoned by communities, marginalized by mainstream agriculture, ignored by research and absent from consumers’ diets, the entire world loses. These traditional crops are usually referred to as Neglected and Underutilized Species (NUS). In order to fully express NUS potential in achieving poverty alleviation, food security and resilience to climate change, priority research and policy actions are needed and many actors need to be involved in the interventions, including farmers, researchers, market chain actors and decision makers. Building greater awareness in minor crops and the opportunities they offer is also an important driver of change.